A generic workflow for effective sampling of environmental vouchers with UUID assignment and image processing. (9th January 2018) - Triebel, Dagmar; Reichert, Wolfgang; Bosert, Simone; Feulner, Martin; Okach, Daniel Osieko; Slimani, Abderachid; Rambold, Gerhard
Abstract: Sampling of biological and environmental vouchers in the field is rather challenging, particularly under adverse habitat conditions and when various activities need to be handled simultaneously. The workflow described here includes five procedural steps, which result in professional sampling and the generation of universally identifiable data. In preparation for the field campaign, sample containers need to be labelled with universally unique identifier (UUID)-QR-codes. At the collection site, labelled containers, sampled material and attached supplementary information are imaged using a GNSS- respectively GPS-enabled smartphone or camera. Image processing, tagging and data storage as CSV text file is subsequently achieved in a field station or laboratory. For this purposes, the newly implemented tool DiversityImageInspector (URL: http://diversityworkbench.net/Portal/DiversityImageInspector ) is used . It addresses combined image and data processing in such a context including the extraction of the QR-coded UUID from the image content and the extraction of geodata and time information from the Exif image header. The import of the resulting data files into a relational database or other kind of data management systems is optional but recommended. If applied, the import might be guided by a data transformation tool with compliant schema as described here. The new approach is discussed also with regard to implications for virtual research environments and data publication networks. Database URL : http://diversityworkbench.net/Portal/DiversityImageInspector